2016
DOI: 10.1590/0074-02760160051
|View full text |Cite
|
Sign up to set email alerts
|

Influence of IL-6, IL-8, and TGF-β1 gene polymorphisms on the risk of human papillomavirus-infection in women from Pernambuco, Brazil

Abstract: Human papillomavirus (HPV) infections are strongly associated with the development of cervical intraepithelial neoplasias and invasive cervical cancer. Polymorphisms in cytokine-encoding genes and behavioural cofactors could play an important role in protecting an individual against viral infections and cancer. Here, we investigated whether IL-6 -174 G>C, IL-8 +396 G>T, and TGF-β1 +869 G>C and +915 G>C polymorphisms were associated with susceptibility to HPV infection in women from north-east (Pernambuco) Braz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The association of IL-6 -174G>C polymorphism with high HPV viral load was not detected. De Lima Júnioret et al showed no difference in the frequency of the -174G>C (rs 1800795) polymorphism in Brazilian women infected with HPV and uninfected controls ( 36 ) which is in agreement with our findings. At the same time, several studies reported a relationship between presences of -174C allele and low-level expression of IL-6 which led to an increase in the risk of cervical cancer ( 37 , 38 ).…”
Section: Discussionsupporting
confidence: 93%
“…The association of IL-6 -174G>C polymorphism with high HPV viral load was not detected. De Lima Júnioret et al showed no difference in the frequency of the -174G>C (rs 1800795) polymorphism in Brazilian women infected with HPV and uninfected controls ( 36 ) which is in agreement with our findings. At the same time, several studies reported a relationship between presences of -174C allele and low-level expression of IL-6 which led to an increase in the risk of cervical cancer ( 37 , 38 ).…”
Section: Discussionsupporting
confidence: 93%
“…Junior's study data shows any significant association between the IL-6+174G>C polymorphism and HPV infected women or uninfected controls or between HSIL and LSIL subgroups. However, taking into account the fact that individuals from the control group could have been previously infected by HPV that was spontaneously eliminated, and based on findings, Junior and colleagues hypothesized that the IL-8 + 396 G allele and GG genotypes could play a role in the risk of HPV infection in a Brazilian study population [20].…”
Section: Discussionmentioning
confidence: 99%
“…In this meta-analysis different case-control groups or cohorts in one publication were considered as independent total of 59 studies were included in this meta-analysis. There are seven studies with 1112 cases and 1233 controls on XRCC3 rs861539 (He et al, 2008;Xiao, 2009;Settheetham-Ishida et al, 2011;Djansugurova et al, 2013;Pérez et al, 2013;Al-Harbi et al, 2017), 14 studies with 2694 cases and 3349 controls MTHFR rs1801133 (Lambropoulos et al, 2003;Sull et al, 2004;Kang et al, 2005;Zoodsma et al, 2005;Delgado-Enciso et al, 2006;Ma et al, 2006;Nandan et al, 2008;Shekari et al, 2008;Kohaar et al, 2010;Yang et al, 2011;Prasad and Wilkhoo, 2011;Tong et al, 2011;Mostowska et al, 2011;von Keyserling et al, 2011), four studies with 1121 cases and 1109 controls on IL-12B rs3212227 (Chen et al, 2009;Do Carmo Vasconcelos De Carvalho et al, 2012;Roszak, Mostowska, et al, 2012), seven studies with 1452 cases and 2186 controls on IL-6 rs1800795 (Nogueira De Souza et al, 2006;Gangwar et al, 2009;Grimm et al, 2011;Shi et al, 2013;de Lima Júnior et al, 2016;Pu et al, 2016;Zidi et al, 2017), 20 studies with 4,781 cases and 4909 controls on TNF-α rs1800629 (Stanczuk et al, 2019;Jang et al, 2001;Calhoun et al, 2002;Gostout et al, 2003;…”
Section: Data Extractionmentioning
confidence: 99%